(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
The character of distribution of chemical elements in ores, оrе concentrates, monomineral fractions, industrial tails and ore surrounding rocks of Thukhmanuk gold deposit have been studied. It is established, that during the process of extraction in structure of tails more than 0․5 g/t of gold and 1 g/t of silver remains. It is also established that ore surrounding rocks contain industrial gold, which can be characterised as additional sources of gold.